Aktual'nye problemy nauchnykh issledovanii v sportivnom plavanii 1980 - 1990 gg. - Bulgakova, N. Z. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The author gives the retrospective analysis of topical problems in theory and technologies of sports swimming which had been studied at the last two decades and an overview on the main achievements of the sports science at the above mentioned period.